Optimal myelin elongation relies on YAP activation by axonal growth and inhibition by Crb3/Hippo pathway - Ruani N. Fernando (Nature Portfolio, 2016)
Molecular mechanisms regulating optimal myelin geometry are only partially understood. Here authors show that peripheral myelin growth is orchestrated by the Crb3/Hippo/YAP pathway, and that defects in YAP activation may underlie peripheral neuropathies caused by shorter myelin.